If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3 = -5x + 3 Reorder the terms: 3 + 4x = -5x + 3 Reorder the terms: 3 + 4x = 3 + -5x Add '-3' to each side of the equation. 3 + -3 + 4x = 3 + -3 + -5x Combine like terms: 3 + -3 = 0 0 + 4x = 3 + -3 + -5x 4x = 3 + -3 + -5x Combine like terms: 3 + -3 = 0 4x = 0 + -5x 4x = -5x Solving 4x = -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 4x + 5x = -5x + 5x Combine like terms: 4x + 5x = 9x 9x = -5x + 5x Combine like terms: -5x + 5x = 0 9x = 0 Divide each side by '9'. x = 0 Simplifying x = 0
| x/5-6=10 | | 3(x+4)=2(2x-3) | | -3m-1=-25 | | 6y-1=27+y | | -7x+9x-3x+6-4+13x=18 | | 8k^2+24k-66=0 | | 5x+10y-15=0 | | 12x=36x^2 | | -4-9=-13 | | 6k^2+48k+90=0 | | 4(x+4)+3(x-1)=-15 | | 3(2g+1)-2(g+5)= | | 27x+17=-30 | | eEx=36 | | 15x+21=7x-19 | | x^3+4= | | 64x=24 | | 25x^2+165x+200=0 | | 40a^2+195a+140=0 | | 135-v=223 | | 11e-4e= | | 6x+10=-56-5x | | 226=-y+163 | | 6x+50=13x-8 | | fx=-2/7×2 | | 6+n=6n | | 84=-u+270 | | 3n^2+24n+21=0 | | fx=-2/7x | | y=1/2(6)+2 | | -2x+4=-6+4 | | 3x-8=6x-14 |